2023
DOI: 10.1590/1414-431x2023e12466
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin ameliorates loperamide-induced functional constipation in mice

Abstract: Functional constipation (FC) is one of the most common gastrointestinal disorders characterized by hard stools and infrequent bowel movements, which is associated with dysfunction of the enteric nervous system and intestinal motility. Luteolin, a naturally occurring flavone, was reported to possess potential pharmacological activities on intestinal inflammation and nerve injury. This study aimed to explore the role of luteolin and its functional mechanism in loperamide-induced FC mice. Our results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…The reduction of the density of hpChAT-ir neurons and fibers is likely to due to the decrease in peripheral cholinergic innervation as the number of HuC/D labeled myenteric neurons was not significantly changed. Such findings provide anatomical support underpinning the alterations of cholinergic transmission previously reported after loperamide treatment-induced constipation ( Kim et al, 2019a , b ; Wang et al, 2023 ). In naïve rats, loperamide reduced acetylcholine esterase activity and the expression of muscarinic cholinergic M2 and M3 receptors in the colon ( Kim et al, 2019a , b ) and in mice, the level of acetylcholine in the colonic tissue was decreased after repeated loperamide-induced functional constipation ( Wang et al, 2023 ).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The reduction of the density of hpChAT-ir neurons and fibers is likely to due to the decrease in peripheral cholinergic innervation as the number of HuC/D labeled myenteric neurons was not significantly changed. Such findings provide anatomical support underpinning the alterations of cholinergic transmission previously reported after loperamide treatment-induced constipation ( Kim et al, 2019a , b ; Wang et al, 2023 ). In naïve rats, loperamide reduced acetylcholine esterase activity and the expression of muscarinic cholinergic M2 and M3 receptors in the colon ( Kim et al, 2019a , b ) and in mice, the level of acetylcholine in the colonic tissue was decreased after repeated loperamide-induced functional constipation ( Wang et al, 2023 ).…”
Section: Discussionsupporting
confidence: 84%
“…Such findings provide anatomical support underpinning the alterations of cholinergic transmission previously reported after loperamide treatment-induced constipation (Kim et al, 2019a,b;Wang et al, 2023). In naïve rats, loperamide reduced acetylcholine esterase activity and the expression of muscarinic cholinergic M2 and M3 receptors in the colon (Kim et al, 2019a,b) and in mice, the level of acetylcholine in the colonic tissue was decreased after repeated loperamide-induced functional constipation (Wang et al, 2023). Likewise, in healthy isolated tenia coli muscle, loperamide decreased the release of acetylcholine produced by electrical field stimulation (Burleigh, 1988).…”
Section: Loperamide Reduced the Cholinergic Innervation Of The Pig Co...supporting
confidence: 85%
See 1 more Smart Citation
“…In line with this, a similar study has confirmed the involvement of 5-HT pathway and alteration of the gut microbiota in alleviating constipation by Ligilactobacillus salivarius Li01 ( Qiu et al, 2022 ). Further evidence supporting this finding comes from studies in constipated-rats demonstrating the laxative effects of herbal extracts, including hot water extract of M. oleifera leaves ( Li et al, 2023 ) and Chinese medicine Houpo Paiqi mixture ( Wang J. et al, 2023 ), were related to gastrointestinal motility and intestinal fluid secretion via the modulation of 5-HT pathway. Another study also indicated that the yellow tea extract consumption protected against operamide-induced constipation in mice partially through the upregulation of 5-HT3 and 5-HT4 expression and downregulation of AQP3 and AQP4 expression in the colon ( Cao et al, 2021 ).…”
Section: Role Of Aqp3 In Constipation and Regulation Of Laxatives On ...mentioning
confidence: 86%
“…AQPs are a family of water channel proteins distributed in the intestinal epithelial cells that play an important role in controlling faecal water content and are associated with the development of constipation [ 20 ]. To date, thirteen types of AQPs (AQP0–AQP12) have been identified in mammals, and several AQPs are aberrantly expressed in STC mice, including AQP3, AQP4, AQP8, and AQP9 [ 21 , 22 ]. Moreover, as research on the brain-gut axis has increased over the past few years, that the intricate link between the pathogenesis of constipation and gut microbiota dysbiosis has become increasingly evident [ 23 ].…”
Section: Introductionmentioning
confidence: 99%